Chronic illness and the personal construction of self: the case of Myalgic Encephalomyelitis - Weinberg, Mark (Department of Psychology, 2023)
Myalgic Encephalomyelitis (ME) has attracted a great deal of media attention in recent years, resulting in a fallacious term, 'Yuppie Flu', being publicly identified with the syndrome. In addition, many studies have identified ME as psychological in origin. Thus, despite increasing evidence that ME has a viral, immunological or neurological aetiology, such negative p_ublicity has led to people with ME experiencing negative reactions from medical doctors and lay-people who have regarded them as depressed at best, an,d malingerers at worst. Hence, a number of questions arise; including: What is the effect of·such negative reaction on the self-concepts of sufferers? Did diagnosis improve self-concept? What effect does a negative public view of ME have on the self-concepts of sufferers? To test these questions, a rating-style repertory grid was drawn up after semistructured interviews with a sample of fifteen diagnosed ME sufferers and was administered to a larger sample of fifty people with ME. The results of this retrospective study indicate that a change in self-concept had indeed occurred since contracting ME, but diagnosis has no effect on this change in self-concept and ME sufferers actually identify themselves in the same terms as they perceive their public stereotype. Reasons for these findings are discussed with reference to both Personal Construct Theory and, as a post hoc explanatory tool, Social Identity Theory.